Synthesis of 2-Substituted 1,2,3-Triazoles of 3-Propargylquinazolone-4 - Akhmadbekovich, Muzaffarov Adil; Abduqayumovich, Abdukahhor Usmonov (American Journal of Biology and Natural Sciences, 2025)
This study is devoted to the synthesis of 1,2,3-triazoles derived from 3-propargylquinazolone-4. A convenient method has been developed for obtaining 2-substituted 1,2,3-triazoles of 3-(prop-2-ynyl)quinazolone-4. The article presents data on the influence of solvents on the yield of the final product.